Plasma membrane proteomic analysis by TMT-PRM provides insight into mechanisms of aluminum resistance in tamba black soybean roots tips - Wei, Yunmin (PeerJ, 2020)
Aluminum (Al) toxicity in acid soil is a worldwide agricultural problem that inhibits crop growth and productivity. However, the signal pathways associated with Al tolerance in plants remain largely unclear. In this study, tandem mass tag (TMT)-based quantitative proteomic methods were used to identify the differentially expressed plasma membrane (PM) proteins in Tamba black soybean (TBS) root tips under Al stress. Data are available via ProteomeXchange with identifier PXD017160. In addition, parallel reaction monitoring (PRM) was used to verify the protein quantitative data. The results showed that 907 PM proteins were identified in Al-treated plants. Among them, compared to untreated plants, 90 proteins were differentially expressed (DEPs) with 46 up-regulated and 44 down-regulated (fold change > 1.3 or < 0.77, p < 0.05). Functional enrichment based on GO, KEGG and protein domain revealed that the DEPs were associated with membrane trafficking and transporters, modifying cell wall composition, defense response and signal transduction. In conclusion, our results highlight the involvement of GmMATE13, GmMATE75, GmMATE87 and H(+)-ATPase in Al-induced citrate secretion in PM of TBS roots, and ABC transporters and Ca(2+) have been implicated in internal detoxification and signaling of Al, respectively. Importantly, our data provides six receptor-like protein kinases (RLKs) as candidate proteins for further investigating Al signal transmembrane mechanisms.